CEO Empowering Leadership and Corporate Entrepreneurship: The Roles of TMT Information Elaboration and Environmental Dynamism - Li, Zhengfei; Chen, Huangen; Ma, Qiuying; Li, Haibo (Frontiers in Psychology, 2021)
We investigate the relationship between CEO empowering leadership and corporate entrepreneurship; Moreover, the mediating role of information elaboration in top management teams (TMTs) and the moderating role of environmental dynamism are examined. Drawing on the information exchange/sharing perspective, we hypothesize that CEO empowering leadership has a positive effect on corporate entrepreneurship and the TMT information elaboration mediates the relationship above. Further, we find that environmental dynamism positively moderates the relationship between empowering leadership and information elaboration, and negatively moderates the relationship between information elaboration and corporate entrepreneurship. Data from a sample of Chinese firms provides empirical evidence in support of these hypotheses.